Formação e expansão da cooperativa agroindustrial - COASUL no Sudoeste do Paraná (1969-2012) - Casagrande, Letícia Risso (2014)
Tried to analyze this work the formation and expansion of COASUL - Cooperativa Agroindustrial, between the years 1969 and 2012 for both, a split was structured in three dissertation chapters, and the first one is a general historical overview of the formation of cooperatives, both worldwide, national and regional, seeking to identify where the roots of the cooperative movement, especially the agricultural sector, in each of these scales. In the second chapter worked with the Brazilian economic outlook from the 1960s, showing the different government policies and the reflection of this for the development of agricultural cooperatives. In the third chapter we sought to examine the emergence and development of COASUL over the years, drawing a parallel cooperative with the national economy. It was observed that the trajectory of the cooperative was already being written with the economic cycles of the country. The first years of activity until the 1980s the COASUL underwent an expansion process, assisting in the modernization of agriculture in southwestern Paraná. During the 1990s suffered from the crisis in obtaining credit situation outlined from the 2000s to new political and economic landscape of Brazil.